A Writing Program in Intermediate Accounting. - Chatfield, Michael (The Accounting Review, 1968)
Narrative writing is neglected in the usual undergraduate accounting program. The general emphasis on objective tests encourages students to consider theoretical discussions of secondary importance or even to equate accounting proficiency with problem solving ability. To meet this problem, a number of universities have introduced writing programs into their undergraduate accounting courses. Usually these include research paper assignments or class essay quizzes. Each quiz relates to the major subject area most recently covered in the text and class discussion, with students given about twice the writing time allowed Certified Public Accountant (CPA) aspirants suggested by the examiners. The use of essay questions from the CPA exam does not anticipate that every student in the program will become a professional accountant. But more importantly, CPA exams provide an unlimited supply of pretested theory questions which are often more realistic than the usual textbook situations. While the program's success is hard to judge objectively, the average quality of papers, as measured by number of points awarded, improves throughout the quarter, with the largest increase coming between the first two quizzes.